Spectacles with highly aspherical lenslets for myopia control do not change visual sensitivity in automated static perimetry - Gao, Yi; Spiegel, Daniel P.; Muzahid, Izzah Al Ilma; Lim, Ee Woon; Drobe, Björn (Frontiers in Neuroscience, 2022)
Abstract Purpose: Spectacle lenses with arrays of lenslets have gained popularity in myopia control due to their high efficacy, low impact on visual performance, and non-invasiveness. One of the questions regarding their impact on visual performance that still remain is that: do the lenslets impact visual field sensitivity? The current study aims to investigate the impact of wearing spectacle lenses with highly aspherical lenslets (HAL) on the visual field sensitivity. Methods: An automated static perimetry test (Goldman perimeter target III) was employed to measure the detection sensitivity in the visual field. Targets were white light dots of various luminance levels and size 0.43°, randomly appearing at 76 locations within 30° eccentricity. Twenty-one adult subjects (age 23 to 61, spherical equivalent refractive error (SER) -8.75 D to +0.88 D) participated in the study. Sensitivities through two lenses, HAL and a single vision lens (SVL) as the control condition, were measured in random order. Results: The mean sensitivity differences between HAL and SVL across the 76 tested locations ranged between -1.14 decibels (dB) and 1.28 dB. Only one location at 30° in the temporal visual field reached statistical significance (p < 0.00065) whereby the sensitivity increased by 1.1 dB with HAL. No significant correlation was found between the difference in sensitivity and age or SER. Such a difference is unlikely to be clinically relevant. Conclusions: Compared to the SVL, the HAL did not change detection sensitivity to static targets in the whole visual field within 30° eccentricity.